Repeated Simulation-based Training for Performing General Anesthesia for Emergency Cesarean Delivery: Long-term Retention and Recurring Mistakes. Issue 4 (December 2015) - Ortner, C.M.; Richebé, P.; Bollag, L.A.; Ross, B.K.; Landau, R.
Abstract : ( Int J Obstet Anesth . 2014;23(4):341–347)